MUHAMMAD SYAHRUR: IMPLEMENTASI TEORI HUDUD DALAM TAFSIR AL-QUR’AN - Ahmad Ridwan Nasution; Irwansyah (JURNAL CERDAS HUKUM, 2023)
Islamic law is required to be able to answer all problems that occur today. There needs to be a new innovation in getting the law out of the Koran. This is what an Arab thinker named Muhammad Syahrur did. He established a theory in interpretation of the Koran. This theory is named after the theory of huddle (limit). This theory is a new theory that in the golden age of Islam itself never came across. For this it is interesting to examine how the huddle theory of interpretation of the Quran can answer the problems that arise in the midst of modern society today. For this reason, the author will create articles using library research methodology (library research) in answering this problem. Thus a conclusion was reached that God's law had a minimum limit and a maximum limit. Keywords: Muhammad Syahrur, hududud, Islamic Law